Identifying talented track and field athletes: The impact of relative age effect on selection to the Spanish National Athletics Federation training camps. Issue 22 (17th November 2017) - Brazo-Sayavera, Javier; Martínez-Valencia, María Asunción; Müller, Lisa; Andronikos, Georgios; Martindale, Russell J. J.
ABSTRACT: This study examined the impact of relative age effect (RAE) on selection to the Spanish National Athletics Federation (RFEA) training camps (TC) between 2006 and 2013. Overall, 1, 334 selected athletes at U15 years (cadet) and U17 years (juvenile) were compared against 27, 711 licensed but unselected athletes for the same age groups. The results highlighted the influential role of the RAE on selection to national level track and field training camp opportunities. Interestingly, this effect was mediated by age and gender, where effects were stronger for both males and younger athletes (U15), with no evidence of RAE for older (U17) female athletes. These results support the "maturation-selection" hypothesis as a mechanism for RAE. Particularly given the long-term goals of RFEA (e.g., production of successful senior elite athletes), these results highlight the need to consider the impact of current selection processes on effective provision of opportunities to those athletes with most potential to succeed in the long term. A number of possible context-relevant solutions are discussed, including education and awareness raising, using holistic selection criteria and correction adjustments techniques.